2014
DOI: 10.1121/1.4890663
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dosage and duration of auditory training for older adults with hearing impairment

Abstract: This study explored a range of training dosages and durations for a word-based auditory-training procedure for older adults with hearing impairment. Three groups received a different “dose”: 2x/week; 3x/week; no training. Fifteen training sessions comprised a “cycle” which was repeated three times for each dosage. Groups that completed training performed significantly better than controls for speech-in-noise materials included in the training regimen, with no significant difference observed between the 2x or 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 12 publications
1
17
1
2
Order By: Relevance
“…Total amount of training time is reported here as previous studies suggest that this might matter more than frequency or duration of training . Despite identical instructions, the filtered training group collectivity spent a greater amount of time on training than the unfiltered group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total amount of training time is reported here as previous studies suggest that this might matter more than frequency or duration of training . Despite identical instructions, the filtered training group collectivity spent a greater amount of time on training than the unfiltered group.…”
Section: Discussionmentioning
confidence: 99%
“…Total amount of training time is reported here as previous studies suggest that this might matter more than frequency or duration of training. 26,27 Despite identical instructions, the filtered training Another limitation is that the study relied on the patient's own audio equipment, and therefore, it was not possible to control sound quality and loudness in the training setting. By omitting the need of specific equipment beyond training CDs, however, the approach proposed and evaluated here is very cost-effective.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…Burk and Humes (2008), for example, found that auditory training led to improved word recognition for trained words but no improvement for recognition of untrained words. Of course, in addition to each of these types of specificity (task, talker, and stimulus), benefits also may be affected by other factors, such as the nature of the training regimen, including "dosage" (see Humes, Kinney, Brown, Kiener, & Quigley, 2014), which is another variable to consider when predicting the probable learning outcomes of auditory training programs.…”
Section: How Effective Is Auditory Training?mentioning
confidence: 99%
“…Reviews of previous results with speech-perception training support the conclusions that speech-perception training results in (1) modest gains on the trained tasks, (2) some generalization to untrained materials, (3) good retention of trained improvements, and (4) favorable attitudes expressed by the participants toward the training experience. 2,[22][23][24][25][26][27][28][29] Evidence of dramatic general improvements in speech perception by hearing-impaired listeners after training is still lacking, and some studies lack appropriate control groups and sufficient sample sizes to assess individual differences. The reported gains are often accompanied by considerable variation from test to test and between individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews of these efforts can be found elsewhere. 2,[22][23][24][25][26][27][28][29] Despite these efforts, auditory training, more specifically, speech-perception training, has not become a standard part of audiological practice. We believe that one reason for this is the lack of a definitive, wellcontrolled, and carefully implemented definitive study of the efficacy of speech-perception training to determine whether, and for which individuals, speech-perception training might be an effective way to improve the success of hearing aid use.…”
mentioning
confidence: 99%